Comparative studies with various substrains of Mycobacterium bovis BCG on the production of an antigenic protein, MPB70. - Miura, K (1983)
A protein, isolated and purified from the unheated culture filtrate of Mycobacterium bovis BCG (substrain Tokyo 172) and designated MPB70, elicited a delayed skin reaction in guinea pigs sensitized with viable cells of BCG but not in those sensitized with heat-killed cells. The skin reaction reached the maximum 4 to 8 weeks after the inoculation of the BCG and then decreased gradually, resulting in conversion to negative after 20 weeks, whereas the skin reaction to purified protein derivative (PPD) continued to be positive. Guinea pigs immunized with viable cells of various substrains of BCG were skin tested with MPB70 and PPD. Guinea pigs immunized with the BCG substrain Tokyo 172 and the substrain Moreau (Brazil) showed strong delayed skin reactions to both MPB70 and PPD. On the other hand, guinea pigs immunized with the Pasteur substrain 1173P2, the Glaxo substrain 1077, the Copenhagen substrain 1331, the Tice substrain, or the Beijing substrain 64-42 showed negative skin reactions to MPB70, whereas they were strongly positive to PPD. In a two-dimensional acrylamide gel electrophoretic analysis of proteins from the culture filtrates of the BCG substrains, the culture filtrates of the Tokyo and Moreau substrains showed the spot of MPB70 on the gel slabs, whereas those of the other BCG substrains did not.